2003
DOI: 10.1002/j.1556-6978.2003.tb01836.x
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Counselor Competency

Abstract: Counselor educators need to be able to demonstrate their effectiveness in training new counselors; however, currently few valid or reliable measures exist for assessing educators' impact. The authors describe the development of such an instrument, the Counseling Skills Scale. They began by revising an existing scale and then they solicited feedback from experts and a focus group. They used the instrument to compare beginning counselors‐in‐training with those who had completed a counseling skills course. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Effect sizes ranged from medium to high. Eriksen and McAuliffe (2003) found that scores for students in a Theories and Techniques course changed significantly in a positive direction on the overall score on the SCS and for all subscales except Develops the Therapeutic Relationship. The effect size was .80, indicating that the change was meaningful.…”
Section: Measures Of Individual Counseling Skillsmentioning
confidence: 90%
See 2 more Smart Citations
“…Effect sizes ranged from medium to high. Eriksen and McAuliffe (2003) found that scores for students in a Theories and Techniques course changed significantly in a positive direction on the overall score on the SCS and for all subscales except Develops the Therapeutic Relationship. The effect size was .80, indicating that the change was meaningful.…”
Section: Measures Of Individual Counseling Skillsmentioning
confidence: 90%
“…The Counseling Skills Scale ( Eriksen & McAuliffe, 2003 ). In 2003, Eriksen and McAuliffe revised the SCS to develop the Counseling Skills Scale (CSS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have developed and examined a variety of assessments to measure students' counseling competencies, assessing skills such as verbal response modes, nonverbal behaviors, and facilitative conditions in counseling (e.g., Counseling Skills Scale [CSS], Eriksen & McAuliffe, 2003;Skilled Counseling Scale [SCS], Urbani et al, 2002), and comprehensive measures that include counseling skills, dispositions, and behaviors (e.g., Counseling Competencies Scale; Swank, Lambie & Witta, 2012). However, counselor educators have used these assessments solely to measure the performance of counseling students after they are enrolled in preparation programs, instead of also integrating them within the admissions process.…”
Section: Why Gatekeep During the Admission Process?mentioning
confidence: 99%
“…Counselor educators have developed several assessments to measure counseling competencies (e.g., Counseling Skills Scale [CSS], Eriksen & McAuliffe, 2003;Skilled Counseling Scale [SCS], Urbani et al, 2002;Counseling Competencies Scale [CCS], Swank, et al, 2012). However, these instruments have not been used to screen applicants.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%